Analysis of Factors Affecting Financial Performance and Managerial Ownership with Governance Moderation of Dividend Policy - Farhan Ady Pratama; Arry Eksandy; Lutfi Zulfa Mazida; Nia Anjani Syarafina (SEAN Institute, 2026)
Financial performance and dividend policy are important factors that influence a company’s sustainability and investor confidence, particularly in the manufacturing sector during periods of economic uncertainty. The COVID-19 pandemic created operational disruptions, reduced purchasing power, and pressured corporate profitability, which consequently affected dividend distribution decisions. This study aims to analyze the relationship between financial performance, managerial ownership, and dividend policy in manufacturing companies. The research employed a quantitative approach using secondary data obtained from company financial statements. Financial performance was measured through profitability, liquidity, solvency, and efficiency ratios, including Return on Equity, Return on Assets, Net Profit Margin, Current Ratio, Quick Ratio, Debt-to-Equity Ratio, and Debt Service Coverage Ratio. The analysis was conducted to evaluate the company’s financial condition and its implications for dividend policy decisions. The findings indicate that strong financial performance encourages more consistent dividend distribution and strengthens shareholder confidence, while managerial ownership contributes to managerial decision-making related to dividend policy. The study concludes that companies need to maintain balanced financial strategies to achieve sustainable growth, preserve financial flexibility, and fulfill shareholder expectations in dynamic economic conditions.